2002
DOI: 10.1046/j.1524-475x.2002.10804.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucan stimulates human dermal fibroblast collagen biosynthesis through a nuclear factor‐1 dependent mechanism

Abstract: Glucan, an immunomodulator, has been reported to increase collagen deposition and tensile strength in experimental models of wound repair. Previous data suggest that glucan modulates wound healing via an indirect mechanism in which macrophages are stimulated to release growth factors and cytokines. However, recent data have shown the presence of glucan receptors on normal human dermal fibroblasts, suggesting that glucans may be able to directly stimulate fibroblast collagen biosynthesis. To test this hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 38 publications
2
51
0
5
Order By: Relevance
“…Polymers of yeasts cell wall exhibit an ability to adsorb harmful chemical substances, for example, mycotoxins, they lower the level of cholesterol and triglycerides in blood, act in anti-mutagenic, anticancerous, antioxidative way, and protect against UV radiations [17,29,41,45,54]. According to other authors [55], b-glucan of yeast origin stimulates collagen biosynthesis which is a significant component in wound-healing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers of yeasts cell wall exhibit an ability to adsorb harmful chemical substances, for example, mycotoxins, they lower the level of cholesterol and triglycerides in blood, act in anti-mutagenic, anticancerous, antioxidative way, and protect against UV radiations [17,29,41,45,54]. According to other authors [55], b-glucan of yeast origin stimulates collagen biosynthesis which is a significant component in wound-healing process.…”
Section: Introductionmentioning
confidence: 99%
“…They recognize b-glucans and mannoprotein as pathogen-associated molecular patterns (PAMPs) [31,45]. Significance of polysaccharides of cell wall in yeasts in stimulation of immunological response, antibacterial activity as well as probiotic one with respect to beneficial microflora of alimentary tract is emphasized [6,9,13,26,37,40,47,51,55]. Polymers of yeasts cell wall exhibit an ability to adsorb harmful chemical substances, for example, mycotoxins, they lower the level of cholesterol and triglycerides in blood, act in anti-mutagenic, anticancerous, antioxidative way, and protect against UV radiations [17,29,41,45,54].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their potent stimulatory effect on macrophages, they increase the cytotoxicity and phagocytic capacity of macrophages (12). Literature reports indicate that beta-glucans exhibit antioxidant, antiviral, antibacterial, and antifungal activities, and have an ameliorative effect on wounds (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The enzyme activity plays an important role in the recycling of proline mostly derived from degradation products of collagen [29]. Wei et al [30] have been reported that glucan stimulates human dermal fibroblast collagen biosynthesis through a nuclear factor-1 dependent mechanism. In our study, we did not find any difference between patients and controls in terms of prolidase activity.…”
Section: Discussionmentioning
confidence: 99%